PRINCIPAL COMPONENT ANALYSIS BIPLOT GLOBAL COMPETITIVENESS INDEX ASEAN COUNTRIES - Pardomuan Robinson Sihombing; Lisna Sari (Jurnal Litbang Edusaintech, 2022)
ASEAN's global competitiveness requires institutional and ASEAN countries appear to be a formidable economic actors in protecting the economic interests and at the same time having an open economic system that indicates the readiness of ASEAN to compete with the economic strength of the entire region in the world. In this case the measurement of global competitiveness factors become important aspects of state enterprises in the face of global competition. This study was conducted to determine how competitive the ASEAN countries with Biplot method of Principal Component Analysis. Results obtained from this study is the ASEAN countries have different advantages in each of the variables related to the global competitiveness index. In addition, the diversity of which can be explained more than 70% which is 90.69% which means that Principal Component Analysis Biplot describes well the overall total.